2017
DOI: 10.1002/jbm.b.33984
|View full text |Cite
|
Sign up to set email alerts
|

Poly(glycerol sebacate) combined with chondroitinase ABC promotes spinal cord repair in rats

Abstract: This study was to investigate the feasibility of PGS combined with ChABC for repairing the transection of spinal cords (TSC) in rats. A thoracic 10 (T10) TSC model of rats was employed. The effects of PGS with ChABC on the morphology and histological structure of the spinal cords, Basso, Beattie, Bresnahan (BBB) scores, and the expression of GAP-43 and NF-200 were comparatively studied. The BBB scores indicated that all rats with TSC were paralyzed immediately after surgery and then recovered hind limb movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Poly­(glycerol sebacate) (PGSeb) modified by grafting of poly­(methyl methacrylate) has been proposed as candidates for nerve tissue engineering Electrospun nanofibers of PMMA–PGSeb in blends with gelatin supported differentiation of PC12 cells onto neuron like phenotypes. Unmodified PGSeb has also been shown a promising material on nerve regeneration in vivo . On animal models, PGSeb was implanted onto spinal cord defects along a promoter of neuron development (ChABC), and the nerve regeneration and functional recovery was evaluated.…”
Section: Prospective Applications Of Polyestersmentioning
confidence: 99%
“…Poly­(glycerol sebacate) (PGSeb) modified by grafting of poly­(methyl methacrylate) has been proposed as candidates for nerve tissue engineering Electrospun nanofibers of PMMA–PGSeb in blends with gelatin supported differentiation of PC12 cells onto neuron like phenotypes. Unmodified PGSeb has also been shown a promising material on nerve regeneration in vivo . On animal models, PGSeb was implanted onto spinal cord defects along a promoter of neuron development (ChABC), and the nerve regeneration and functional recovery was evaluated.…”
Section: Prospective Applications Of Polyestersmentioning
confidence: 99%
“…A simple, porous PGS film proved to promote motor function recovery through nerve generation by enhancing axon growth and neuron sprouting in a rat model, where the complete transection of the spinal cord was employed. [ 189 ] These results were even improved if combined with chondroitinase ABC. For nerve TE, electrically conductive grafts have shown great potential.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…However, this technique is constrained due to a restricted supply of donated nerves, the necessity for a second surgery, donor site morbidity, loss of function, a mismatch between donor nerve and recipient site and clinically functional recovery rates of only 80%. [187][188][189] Research within a variety of biological or artificial nerve grafts has been carried out to supplement or even substitute autologous nerve grafts. Nerve grafts have to fulfill several requirements as biocompatibility, biodegradability, permeability, biochemical properties, as well as macro and microarchitecture.…”
Section: Nerve Tementioning
confidence: 99%
“…The device combined three stimulating factors, a micro-patterned surface, a neurotrophic gradient membrane and seeding with Schwann cells, and it was demonstrated that neural stem cells could attach, proliferate, and differentiate successfully on this device. PGSeb was also evaluated for the repair of the transection of spinal cords [163].…”
Section: Other Tissuesmentioning
confidence: 99%